Still kicking : [videorecording (DVD)] : six artistic women of Project Arts & Longevity - Gorman, Amy; Kandl, Frances; Catlett, Frances Dunham, 1908-2014-; Ogata, Elsie, 1912-2015-; Davlin, Ann, 1910-2008-; Gildersleeve, Grace, 1911-2012-; Mason, Madeline, 1902-2007-; Hearst, Lily, 1897-2005 (Golden Bear Casting, 2006)
Amy Gorman and Frances Kandl journey throughout the San Francisco Bay Area searching for female role models--very old women, still active artists, living with zest. While Amy chronicles their oral histories, Frances is inspired to compose songs. Honors the gift of age, and illustrates that growing old can be a time of creative expression and satisfaction.